Exploring the relationship between static and dynamic balance performance through the same center-of-pressure parameters - A. Rizzato; A. Paoli; Giuseppe Marcolin (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The interpretation of evidence on the relationship between static and dynamic balance is complicated due to the several systems involved in postural control and the heterogeneity of the dynamic balance tasks used. The primary aim of this study was to explore the correlation between static and dynamic balance performance among healthy adults by means of the same center-of-pressure parameters. Given the importance of rapid reactive postural response in dynamic conditions, the secondary aim was to explore the relationship between dynamic balance performance and quadriceps strength and power. Methods Thirty-two healthy subjects (18 females; mean ± SD: age = 30.68 ± 13.31 years; body mass = 74.84 ± 15.18 kg; height = 1.75 ± 0.07 m) were assessed in static and dynamic balance conditions through a force plate that allowed computing the center of pressure trajectory. Static balance was assessed during an upright standing test and dynamic balance during an unstable board test. The same center-of-pressure parameters were calculated for both the two balance conditions: the 95th percentile ellipse area (Area95) and center-of-pressure mean velocity (MeanVelocity). The isometric quadriceps strength of the dominant leg was measured at 90 degrees of knee flexion with a load cell in steady and ballistic conditions. The maximal isometric strength and rate of force development were calculated. Results Pearson’s correlation showed non-statistically significant correlations between static and dynamic balance performance for both Area95 (R2 = 0.10; p = 0.07) and MeanVelocity (R2 = 0.001; p = 0.99). Across all parameters, the stepwise multiple linear regression analysis identified the RFD in the 100–150 ms window as the only determinant factor of the Area95 (p < 0.05, adjusted R² = 0.136) and MeanVelocity (p < 0.05, adjusted R² = 0.188) in the dynamic balance condition. Conclusions This study suggests a lack of correlation between static and dynamic balance performance in healthy adults, indicating that both may need to be considered in balance assessments for a more comprehensive evaluation.